Early neurological deterioration in older adults with traumatic brain injury. (March 2018) - Scheetz, Linda J.; Horst, Michael A.; Arbour, Richard B.
Highlights: Fatal TBI incidence in older adults increased significantly worldwide in recent years. Early recognition of neurological deterioration provides opportunities for early intervention. Early recognition mandates accurate use of assessment tools such as the GCS. Early management improves outcomes and is guided by early, accurate GCS scoring. Future research directions include identifying means to improve early detection. Abstract: Introduction: Traumatic brain injuries (TBIs) and resulting fatalities among older adults increased considerably in recent years. Neurological deterioration often goes unrecognized at the injury scene and patients arrive at emergency departments with near-normal Glasgow Coma Scale (GCS) scores. This study examined the proportion of older adults experiencing early neurological deterioration (prehospital to emergency department), associated factors, and association of the magnitude of neurological deterioration with TBI severity. Methods: This secondary analysis of National Trauma Data Bank Research Datasets included patients who were age ⩾65, sustained a TBI, and transported from the injury scene to an emergency department. Data analysis included chi-square analysis, t -tests, and logistic regression. Long-term anticoagulant/antiplatelet therapy was not associated with deterioration. Results: Of the sample of 91, 886 patients, 13, 913 (15.1%) experienced early neurological deterioration. Adjusting for covariates, age, gender, head AISmax injury severity, and probability of death were associated with early deterioration. Patients with severe and critical head injuries had the highest odds of early neurological deterioration (OR = 1.41 [CI = 1.22–1.63] and OR = 1.98 [CI = 1.63–2.40], p  < 0.001). Discussion/conclusions: Prehospital providers, nurses, physicians, and other providers have opportunities to optimize outcomes from older adult TBI through early recognition of neurological deterioration, rapid transport to facilities for definitive treatment, and targeted rehabilitation.